The role of orthodontics in management of obstructive sleep apnea - Reem A. Alansari (Elsevier, 2022)
Dental sleep medicine is the field of dental practice that deals with the management of sleep-related breathing disorders, which includes obstructive sleep apnea (OSA) in adults and children. Depending on the developmental age of the patient and the cause of the apnea dental treatment options may vary. For adult patients, treatment modalities may include oral appliance therapy (OAT), orthognathic surgery and surgical or miniscrew supported palatal expansion. While for children, treatment may include non-surgical maxillary expansion and orthodontic functional appliances. Many physicians and dentists are unaware of the role dentistry, particularly orthodontics, may play in the interdisciplinary management of these disorders. This review article is an attempt to compile evidence-based relevant information on the role of orthodontists/sleep dentists in the screening, diagnosis, and management of sleep apnea. Oral sleep appliance mechanisms of action, selective efficacy, and the medical physiological outcomes are discussed. The purpose of this review is to provide a comprehensive understanding of how orthodontists and sleep physicians can work in tandem to maximize the benefits and minimize the side effects while treating patients with OSA.